Thermal Analysis Simulation of Germanium Zone Refining Process Assuming a Constant Radio-Frequency Heating Source. (May 2016) - Ezheiyan, Mahdi; Sadeghi, Hossein; Tavakoli, Mohammad-Hossein
Abstract : Three-dimensional thermal analysis simulation of a horizontal zone refining system is conducted for germanium semiconductor materials. The considered geometry includes a graphite boat filled with germanium placed in a cylindrical quartz tube. A flow of Ar and H2 gas mixture is purged through the tube. A narrow section of the boat is assumed to be exposed to a constant heat rate produced by an rf coil located outside the quartz tube. The results of this analysis provide essential information about various parameters such as the shape of the molten zone, required power and temperature gradient in the system.